Mimotope peptide modified pompon mum-like magnetic microparticles for precise recognition, capture and biotransformation analysis of rituximab in biological fluids - Jiawen Yang; Aixuan Zhou; Minyi Li; Qiaoxian He; Jingwei Zhou; Jacques Crommen; Wentao Wang; Zhengjin Jiang; Qiqin Wang (Elsevier, 2024)
Due to low immobilized ligand density, limited binding capacity, and severe interference from serum proteins, developing ideal peptide-based biomaterials for precise recognition and in vivo analysis of biopharmaceuticals remains a huge challenge. In this study, mimotope peptide modified pompon mum-like biomimetic magnetic microparticles (MMPs, 3.8 μm) that mimic the specific functionalities of CD20 on malignant B cells were developed for the first time. Benefit from the numerous ligand binding sites (Ni2+) on the pompon mum-like MMPs, these novel materials achieved ≥10 times higher peptide ligand densities (>2300 mg/g) and antibody binding capacities (1380 mg/g) compared to previous reported biomaterials. Leveraging the high specificity of the mimotope peptide, rituximab can be precisely recognized and enriched from cell culture media or serum samples. We also established an LC‒MS/MS method using the MMPs for tracking rituximab biotransformation in patient serum. Intriguingly, deamidation of Asn55 and Asn33, as well as oxidation of Met81 and Met34 were observed at the key complementarity determining regions of rituximab, which could potentially influence antibody function and require careful monitoring. Overall, these versatile biomimetic MMPs demonstrate superior recognition and enrichment capabilities for target antibodies, offering interesting possibilities for biotransformation analysis of biopharmaceuticals in patient serum.